2021
DOI: 10.3389/fimmu.2021.686795
|View full text |Cite
|
Sign up to set email alerts
|

Circulating and Synovial Pentraxin-3 (PTX3) Expression Levels Correlate With Rheumatoid Arthritis Severity and Tissue Infiltration Independently of Conventional Treatments Response

Abstract: AimsTo determine the relationship between PTX3 systemic and synovial levels and the clinical features of rheumatoid arthritis (RA) in a cohort of early, treatment naïve patients and to explore the relevance of PTX3 expression in predicting response to conventional-synthetic (cs) Disease-Modifying-Anti-Rheumatic-Drugs (DMARDs) treatment.MethodsPTX3 expression was analyzed in 119 baseline serum samples from early naïve RA patients, 95 paired samples obtained 6-months following the initiation of cs-DMARDs treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 53 publications
3
12
0
Order By: Relevance
“…In our study, we observed increased levels of both PTX3 and SAP in AS patients, yet we could not demonstrate a relation with disease activity. These results, in accordance with the results of Deniz et al [ 4 ], Boutet et al [ 15 ], and Nisihara et al [ 16 ], may imply that these biomarkers may have diagnostic value in spondyloarthritis, regardless of disease activity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, we observed increased levels of both PTX3 and SAP in AS patients, yet we could not demonstrate a relation with disease activity. These results, in accordance with the results of Deniz et al [ 4 ], Boutet et al [ 15 ], and Nisihara et al [ 16 ], may imply that these biomarkers may have diagnostic value in spondyloarthritis, regardless of disease activity.…”
Section: Discussionsupporting
confidence: 92%
“…Deniz et al [ 4 ] demonstrated increased PTX3 levels in AS patients without any correlation with disease activity. Boutet et al [ 15 ] reported increased PTX3 levels in rheumatoid arthritis patients in comparison to healthy subjects, but again, no relation with active disease was reported. Likewise, Nisihara et al [ 16 ] did not observe any correlation between PTX levels and disease activity in spondyloarthritis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigating the inflammatory mediators in serum of RA-patients, demonstrate a higher level of TWEAK, and Pentraxin-3 compared to controls (Park et al, 2008;Boutet et al, 2021). According to Boutet et al, the serum levels of Pentraxin-3 are correlated with disease activity and may act as a reliable marker of RA activity (Boutet et al, 2021). In addition, expression of IL-19 is also significantly elevated in synovial fluid of patients with RA compared to healthy controls, indicating an involvement of the regulation of synovial inflammation in patients with RA (Alanara et al, 2010).…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies investigating the inflammatory mediators in serum of RA-patients, demonstrate a higher level of TWEAK, and Pentraxin-3 compared to controls (Park et al, 2008;Boutet et al, 2021). According to Boutet et al, the serum levels of Pentraxin-3 are correlated with disease activity and may act as a reliable marker of RA activity (Boutet et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…This limitation may have affected the gene expression signatures and interfered with the interpretation of the fundamental role of some genes in RA pathogenesis. Only a few studies have considered the analysis of treatment-naïve RA patients to identify gene expression signatures in response to treatment and to characterize better the RA transcriptional profiles obtaining insightful results ( Shchetynsky et al, 2017 ; Boutet et al, 2021 ; Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%